Volume 3: Biomedical and Biotechnology Engineering 2014
DOI: 10.1115/imece2014-38152
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Calcified Plaques Retrieved From Occluded Arteries and Comparison With Potential Artificial Analogues

Abstract: Cardiovascular disease is the leading cause of death worldwide. This disease includes chronic total occlusion (CTO), which is a complete blockage of an artery. Unlike partial occlusions, CTOs are difficult to cross percutaneously using conventional guidewires (thin and flexible wires) because of the fibrotic and calcified nature of the blockage. The lack of data regarding the mechanical properties of CTO limits the development of new technologies in the field of percutaneous coronary intervention (PCI) and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Mechanical properties of seven common types of human tissues from prior studies. Data taken from (a) Taylor and Miller (2004) Schoenfeld et al (1974) and (p) Riel et al (2014).…”
Section: Tmm For Soft Tissue In Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical properties of seven common types of human tissues from prior studies. Data taken from (a) Taylor and Miller (2004) Schoenfeld et al (1974) and (p) Riel et al (2014).…”
Section: Tmm For Soft Tissue In Surgical Proceduresmentioning
confidence: 99%
“…To fabricate phantoms with different elastic modulus, softener was added and resulted in elastic modulus of 3-200 kPa (Hungr et al 2012). The mechanical and imaging properties of Hollensteiner et al (2017Hollensteiner et al ( , 2018Hollensteiner et al ( , 2019, (g) Tai et al (2015Tai et al ( , 2016Tai et al ( , 2018, (h) Riel et al (2014), Lyu et al (2019).…”
Section: Human Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…where I 1 and I 2 are the first and second invariants of the Cauchy-Green tensor and a 10 and a 01 are the hyperelastic constants of 18.90 kPa and 2.75 kPa referenced from the experimental data of human femoral artery [22]. A nanoindentation study showed that the elastic modulus of human calcified plaques collected from the superficial femoral artery wall was 20.1 GPa [23].…”
Section: Plos Onementioning
confidence: 99%
“…The highly complex and spatially variable structure of a CTO may also change depending on lesion age. Unfortunately, assessing in vivo morphology and composition of the CTO in fully occluded blood vessels is difficult [17] and only Mathematical Problems in Engineering 3 limited information is available from ex vivo experimental observation [18]. Particularly concerning human studies, a systematic investigation regarding the mechanical behavior and failure properties of CTOs is still lacking.…”
Section: Introductionmentioning
confidence: 99%